Comparative FE-studies of interface behavior of granular Cosserat materials under constant pressure and constant volume conditions - Ebrahimian, B.; Alsaleh, M.I.; Kahbasi, A. (Archives of Mechanics, 2021)
This article shows the outcomes of a systematic series of finite element (FE) calculations relevant to the shear behavior of a particulate-continuum interface system under different normal boundary conditions. In this respect, shearing of a thin and long granular Cosserat layer in the vicinity of a rigid moving wall with varied surface roughness values is analyzed under constant normal pressure and constant volume conditions. The material behavior is defined with a special elasto-plastic Cosserat model, taking into account micro-rotation, micro-curvature, couple stress, and mean particle size. The interaction between the layer of boundary particles and the surface roughness of the adjoining bottom wall is modeled by the rotation resistance of particles along the wall surface. Herein, the coupled effects of normal confining constraints imposed on the layer and the surface roughness of the bottom wall, are considered on the response of granular material under shearing. The influences of pressure level and initial void ratio are explored as well. Numerical results demonstrate that the dilatancy constraint prescribed to the interface plane in the normal direction, and the wall roughness have visible influences on the interface shear resistance as well as the deformation field formed within the layer. After large shearing, the width of the localized zone along the wall does not necessarily depend on the normal confining constraint and the applied pressure level. However, the localized zone characteristics and the interface shear response are mainly affected by the initial void ratio of the material. In addition to FE analyses, DEM-based simulations are also performed to investigate the micro-mechanical response of granular medium adjacent to a wall under shearing. FE predictions are qualitatively compared with DEM results, and reasonable agreement is observed.